Pengembangan E-Learning Berbasis Web Blog pada Mata Pelajaran Matematika Materi Bangun Datar - Siska Kumala Sari; Dodik Mulyono; Elya Rosalina (Journal of Elementary School (JOES), 2023)
The Research Aims To Find Out The Development Of Web-Based E-Learning Learning Media In Mathematics Subjects With Flat Shape Materials That Meet Valid And Practical Criteria. The research method used is research and development which refers to the Addie development model. Based on the results of small group trials conducted in Class IV Sdn 66 Lubuklinggau, it was found that, the results of the practicality of the Web Blog Learning Media are 90% and are in very practical criteria. Then the Validation Trial Conducted by 3 Validators of Media Experts, Language, and Materials, The Result of Media Web Blog Validation Is 0.87 with a High Category. Thus, it can be concluded that in the small group trial phase and the validation test, the criteria for validity and practicality were met. Learning Media Web Blogs on Mathematics Subjects Class IV Elementary Flat Building Materials Can be Used in the Teaching and Learning Process in Elementary Schools Keywords : Flat Wake, E-Learning, Mathematics, Web Blog